Endoscopic Surveillance for Congenital Diaphragmatic Hernia: Unexpected Prevalence of Silent Esophagitis - Morandi, Anna; Macchini, Francesco; Zanini, Andrea; Pasqua, Noemi; Farris, Giorgio; Canazza, Lorena; Gentilino, Valerio; Di Cesare, Antonio; Leva, Ernesto (European Journal of Pediatric Surgery, 2016)
Introduction Gastroesophageal reflux disease (GERD) is a frequent comorbidity after congenital diaphragmatic hernia (CDH) repair. Our aim was to evaluate the clinical and endoscopic prevalence of esophagitis in a long-term follow-up of CDH patients.Materials and Methods Patients operated on for posterolateral CDH and undergoing general anesthesia for concomitant pathologies between January and October 2013 were included in the study. GERD was investigated both clinically (Manterola questionnaire) and endoscopically. The severity of esophagitis was evaluated according to the Hetzel–Dent classification and multiple biopsies were performed. The correlation between clinical score and severity of esophagitis was evaluated.Results Twelve patients were included in the study (mean age: 14.5 years; range, 9–18 years). Only three children (25%) had a pathological questionnaire. At endoscopy, three children (25%) were affected by grade 1 esophagitis, six (50%) by grade 2, two (17%) by grade 3, and one (8%) by grade 4. One of the children presented Barrett esophagus. A moderate negative correlation was found between clinical data and endoscopic findings (r: −0.54 and p: 0.067).Conclusion Even in the absence of symptoms, esophagitis revealed to have a high prevalence in CDH patients. A long-term clinical and instrumental follow-up is mandatory to early diagnose and treat GERD.
Keywords: esophagitis; congenital diaphragmatic hernia; GERD